Analisis Tingkat Literasi Digital Petugas Puskesmas dan Implikasinya Terhadap Efektivitas Layanan Kesehatan Primer - Asharul Fahyudi; Meilinda Asrining Hapsari; Nina Dwi Astuti; Retnowati (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
The advancement of information technology requires primary health care centers (Puskesmas) to adopt digital systems, including electronic medical records. However, the low level of digital literacy among health workers remains a challenge in delivering effective services. This study aimed to analyze the digital literacy level of Puskesmas staff and its implications for the quality of primary health care. A mixed-method cross-sectional design was applied, combining quantitative surveys and qualitative interviews with health workers and Puskesmas heads. The findings revealed significant associations between respondents’ characteristics and digital literacy. Age showed a moderate to strong positive correlation (rs = 0.593; p < 0.001), while education demonstrated a significant negative correlation (rs = -0.413; p = 0.019). Work experience and professional background were not significantly related, whereas access to digital technology and the internet was relatively uniform. Digital literacy was more influenced by age and generational factors, with Generation Z achieving the highest scores, Generation Y dominant at mid-to-high levels, and Generation X tending toward moderate scores.